Identification of the Unique Clinical and Genetic Features of Chinese Lung Cancer Patients With EGFR Germline Mutations in a Large-Scale Retrospective Study - Lin, Xinqing; Peng, Muyun; Chen, Quanfang; Yuan, Mingming; Chen, Rongrong; Deng, Haiyi; Deng, Jiaxi; Liu, Ouqi; Weng, Yuqing; Chen, Mingjiu; Zhou, Chengzhi (Frontiers in Oncology, 2021)
Background: Epidemiological surveys have suggested that lung cancer has inherited susceptibility and shows familial aggregation. However, the distribution and prevalence of epidermal growth factor receptor (EGFR) germline variants and their roles in lung cancer genetic predisposition in the Chinese remain to be elucidated. Methods: In this study, EGFR germline and somatic variants were retrospectively reviewed from the next-generation sequencing results of 31,906 patients with lung cancer. Clinical information was also collected for patients with confirmed EGFR germline mutations. Results: A total of 22 germline EGFR variants were identified in 64 patients with lung cancer, accounting for 0.2% of the total cases studied. Five patients were diagnosed as multiple primary carcinomas. Family history was documented in 31.3% (20/64) patients, 55% of which were diagnosed as lung cancer. G863D was the most frequent EGFR germline mutation, followed by P848L, D1014N, and K757R. Somatic EGFR sensitive mutations were identified in 51.6% of patients with germline EGFR mutations. The proportion of L858R mutation, exon 19 deletion, and rare sensitive mutation was 50%, 17.6%, and 32.4%, respectively. D1014N and T790M mutations were common in young patients. The family members of patients with P848L, R776H, V769M, and V774M mutations were more commonly diagnosed with cancers. A total of 19 patients were confirmed to have received EGFR tyrosine kinase inhibitors (TKIs), but the response to EGFR-TKIs differed among patients with different EGFR mutations. Conclusion: Chinese patients with lung cancer harbored unique and dispersive EGFR germline mutations and showed unique clinical and genetic characteristics, with varied response patterns to EGFR-TKI treatment.